Experimental results of a Mach 10 conical-flow derived waverider to 14-X hypersonic aerospace vehicle - Rolim,Tiago Cavalcanti (2011)
Abstract This paper presents a research in the development of the 14-X hypersonic airspace vehicle at Institute for Advanced Studies (IEAv) from Department of Science and Aerospace Technology (DCTA) of the Brazilian Air Force (FAB). The 14-X project objective is to develop a higher efficient satellite launch alternative, using a Supersonic Combustion Ramjet (SCRAMJET) engine and waverider aerodynamics. For this development, the waverider technology is under investigation in Prof. Henry T. Nagamatsu Aerothermodynamics and Hypersonics Laboratory (LHTN), in IEAv/DCTA. The investigation has been conducted through ground test campaigns in Hypersonic Shock Tunnel T3. The 14-X Waverider Vehicle characteristic was verified in shock tunnel T3 where surface static pressures and pitot pressure for Mach number 10 were measured and, using Schlieren photographs Diagnostic Method, it was possible to identify a leading-edge attached shock wave in 14-X lower surface.